2015
DOI: 10.1002/cne.23910
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptide SIFamide in the brain of three cockroach species

Abstract: The sequence as well as the distribution pattern of SIFamide in the brain of different insects is highly conserved. As a general rule, at least four prominent SIFamide-immunoreactive somata occur in the pars intercerebralis. They arborize throughout the brain and the ventral nerve cord. Whereas SIFamide is implicated in mating and sleep regulation in Drosophila, other functions of this peptide remain largely unknown. To determine whether SIFamide plays a role in the circadian system of cockroaches, we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…Because of its generous size and simple animal maintenance, P. americana is well suited for studying the morphology, physiology, and pharmacology of the insect nervous system. Such research has led to a better understanding of the neural basis of escape behavior [ 4 , 5 ], circadian rhythmicity [ 6 , 7 ], and neuropeptide distribution and action [ 8 , 9 , 10 ]. In addition, various learning paradigms have been established for P. americana during the last few years [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its generous size and simple animal maintenance, P. americana is well suited for studying the morphology, physiology, and pharmacology of the insect nervous system. Such research has led to a better understanding of the neural basis of escape behavior [ 4 , 5 ], circadian rhythmicity [ 6 , 7 ], and neuropeptide distribution and action [ 8 , 9 , 10 ]. In addition, various learning paradigms have been established for P. americana during the last few years [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In P. americana, in addition to the conserved cells in the pars interecerebralis, SIFamidergic cells were also seen in the OLs and posterior protocerebrum (Arendt et al, 2016). Neuronal circuits for SIFamide seemed to be colocalized with pigment-dispersing factor, histamine, and gamma amino butyric acid, suggesting that SIFamide may be involved in regulating rhythmic behavior associated with the circadian system (Arendt et al, 2016). Similarly, immunohistochemical data from D. melanogaster also reveals synapses between the four SIFamidergic neurons and DN1 dorsal clock circadian pacemaker neurons (Cavanaugh et al, 2014), suggesting SIFamide may constitute an element in modulating behaviors governed by the circadian clock.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of extensive SLI in the OLs of R. prolixus may suggest a potential function in mediating rhythmic behavior guided by environmental cues such as locomotion, feeding, and ecdysis (Davey, 2007). In P. americana, in addition to the conserved cells in the pars interecerebralis, SIFamidergic cells were also seen in the OLs and posterior protocerebrum (Arendt et al, 2016). Neuronal circuits for SIFamide seemed to be colocalized with pigment-dispersing factor, histamine, and gamma amino butyric acid, suggesting that SIFamide may be involved in regulating rhythmic behavior associated with the circadian system (Arendt et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…The antiserum has been used in several studies (Sullivan et al, ; van Meer et al, ; Greferath et al, ), one of which demonstrated its reliability in insects (Hamanaka et al, ). Also in R. maderae , liquid‐phase preadsorption of the antiserum with 100 µM of a histamine–BSA conjugate was sufficient to abolish the staining completely (Arendt et al, ). Preadsorption with Rhm ‐corazonin in double‐label experiments had no effect on the histamine staining.…”
Section: Methodsmentioning
confidence: 99%
“…The monoclonal PDF antibody (RRID:AB_760350; Table ) was obtained from cell cultures of hybridoma cells (Cyran et al, ) purchased from the Developmental Studies Hybridoma Bank (Department of Biology, University of Iowa, Iowa City, IA) and has been used in a variety of studies analyzing the circadian system of R. maderae (Soehler et al, ; Wei and Stengl, ; Schulze et al, ; Arendt et al, ). The specificity of this antibody has also been demonstrated with liquid‐phase preadsorption, given that 10 µM of Rhm ‐PDF was sufficient to abolish the staining completely (Schulze et al, 2012).…”
Section: Methodsmentioning
confidence: 99%